The effect of flatter hierarchy on applicant pool gender diversity: Evidence from experiments - Hurst, Reuben; Lee, Saerom (Ronnie); Frake, Justin (Strategic Management Journal, 2024)
Research Summary This article investigates how job seekers' perceptions of an employer's formal hierarchy affect the size and gender composition of its applicant pool. Building on the literature on gendered organizations and organizational design, we develop opposing perspectives on these relationships. To arbitrate between these perspectives, we first conduct a field experiment in partnership with a hiring firm. We find that featuring a flatter hierarchy in recruiting materials does not significantly affect the size of the applicant pool, but significantly decreases women's representation within it. Our follow‐up survey experiment identifies several potential mechanisms (e.g., perceptions of career progression, informality, workload, and fit). Our findings imply that firms' growing tendency to adopt flatter hierarchies could inadvertently undermine efforts to attract a greater proportion of women applicants. Managerial Summary Using a pair of labor market experiments, this study finds that characterizing a hiring firm's hierarchy as “flatter” with fewer management levels reduces women's representation in the applicant pool. We show that this decrease in the share of women applicants is likely driven by the fact that women, compared to men, perceive flatter hierarchies as more likely to present difficulties in fitting in, burden them with more work, and provide fewer opportunities for career progression. These findings suggest that, to mitigate workplace gender segregation, organizations with flatter structures may benefit from de‐emphasizing their organizational hierarchies in recruitment efforts. Moreover, companies should consider how their organizational attributes contribute to fostering a more inclusive work environment.